Activation of P2X4 receptor exacerbates acute brain injury after intracerebral hemorrhage. (30th March 2022) - Wu, Si‐Ting; Han, Jin‐Rui; Yao, Nan; Li, Yu‐Lin; Zhang, Fang; Shi, Yao; Shi, Fu‐Dong; Li, Zhi‐Guo
Abstract: Introduction: Intracerebral hemorrhage (ICH) accounts for 10%–15% of all strokes and culminates in high mortality and disability. After ICH, brain injury is initiated by the mass effect of hematoma, followed by secondary cytotoxic injury from dying brain cells, hematoma disintegration, and cascading brain immune response. However, the molecular mechanism of secondary cytotoxic brain injury in ICH is not completely understood. The sensitive purinergic receptor, P2X4 receptor (P2X4R), was known to recognize extracellular free ATP released by dying cells during tissue injury. Aims: In this study, we aim to understand the role of P2X4R in acute brain injury triggered by ICH. Results: In this study, we found that the sensitive purinergic receptor, P2X4R, was upregulated in the brain of patients with ICH as well as in a mouse model of ICH induced by collagenase injection. P2X4R blockage with the specific inhibitor 5‐BDBD attenuated brain injury in ICH mice by significantly reducing brain edema, blood–brain barrier leakage, neural death, and ultimately acute neurodeficits. Further study indicated that the protective effect of P2X4R inhibition is related to decreased pro‐inflammatory activity of microglia and recruitment of peripheral immune cells into the hemorrhagic brain. Conclusions: These results suggest that the P2X4 receptor is activated by ICH stimuli which worsen brain injury following ICH. Abstract : Intracerebral hemorrhage (ICH) triggers the upregulation of P2X4R in the brain of patients with ICH. P2X4R inhibitor 5‐BDBD can reduce brain injury such as blood–brain barrier (BBB) leakage after ICH in pro‐clinical mouse model.